2015
DOI: 10.3389/fpsyg.2015.01290
|View full text |Cite
|
Sign up to set email alerts
|

The perception of speech modulation cues in lexical tones is guided by early language-specific experience

Abstract: A number of studies showed that infants reorganize their perception of speech sounds according to their native language categories during their first year of life. Still, information is lacking about the contribution of basic auditory mechanisms to this process. This study aimed to evaluate when native language experience starts to noticeably affect the perceptual processing of basic acoustic cues [i.e., frequency-modulation (FM) and amplitude-modulation information] known to be crucial for speech perception i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 79 publications
5
25
0
Order By: Relevance
“…For lexical tones, the same pattern has been observed at around the same age. Infants from a non-tone language background show a perceptual decline for non-native tones between 6 and 9 months, while infants from a tone language background do not show any decline for the same tone contrasts at the same age (Cabrera et al, 2015;Mattock & Burnham, 2006;Mattock, Molnar, Polka, & Burnham, 2008;Yeung, Chen, & Werker, 2012). However, a perceptual rebound for lexical-tone perception has recently been observed in the second year of life for non-native infants (Liu & Kager, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…For lexical tones, the same pattern has been observed at around the same age. Infants from a non-tone language background show a perceptual decline for non-native tones between 6 and 9 months, while infants from a tone language background do not show any decline for the same tone contrasts at the same age (Cabrera et al, 2015;Mattock & Burnham, 2006;Mattock, Molnar, Polka, & Burnham, 2008;Yeung, Chen, & Werker, 2012). However, a perceptual rebound for lexical-tone perception has recently been observed in the second year of life for non-native infants (Liu & Kager, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…As for the attunement of lexical tones, tone-language learning infants maintain and improve their tonal sensitivity ( Harrison, 2000 ; Mattock and Burnham, 2006 ; Yeung et al, 2013 ; Shi et al, 2017a ; Tsao, 2017 ). Meanwhile, non-tone-language learning infants’ sensitivity to tones greatly decreases at 9 months ( Mattock and Burnham, 2006 ; Mattock et al, 2008 ; Liu and Kager, 2014 ; Cabrera et al, 2015 ; Shi et al, 2017b ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that adults may have learned to rely on specific acoustic information such as the fine spectro-temporal cues conveying fine voice-pitch variations in order to perceive lexical tones. Although Mandarin-speaking adults with NH experience difficulties in perceiving lexical tones when the fine spectrotemporal cues are degraded, in non-tone languages, such as French, listeners who have learned to rely on the envelope cues to detect tone differences do not have the same difficulties (Cabrera et al, 2014(Cabrera et al, , 2015. The children in the present study had congenital hearing loss and therefore had been listening to speech only through CI processors after implantation.…”
Section: B Perception Of Lexical Tones and Consonants Using Cismentioning
confidence: 77%
“…This crosslinguistic difference is also observed at 10 months of age; however, it is not observed at 6 months. This observation suggests that the duration of exposure to the native language does influence the use of the acoustic information of the speech signal (Cabrera et al, 2015). Interestingly, in those studies, French listeners (infants at 10 months and adults) were shown to be better able to use the remaining temporal envelope to discriminate non-native lexical tones compared to Mandarin listeners.…”
Section: Ci-simulation Studies and Lexical Tone Perceptionmentioning
confidence: 94%
See 1 more Smart Citation